DAMPAK PANDEMI COVID-19 TERHADAP KEUNTUNGAN WARUNG SAYUR DI LIWAS KELURAHAN RANOMUUT KECAMATAN PAAL DUA KOTA MANADO - Monica Gabriela Tuwaidan; Melsje Yellie Memah; Jenny ., Baroleh (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the advantages of vegetable stalls before and during the Covid-19 pandemic in Liwas, Ranomuut Village, Paal Dua District, Manado City. Located close to the Office of Religious Affairs in Paal Dua District. The time of conducting the research in September 2020 to November 2020. The data used in this study are primary data and secondary data. Primary data was obtained from 4 respondents (traders) and using a list of questions that had been prepared previously. Secondary data were obtained from books, internet, journals and other sources related to the problems in this study. The analysis used is profit analysis. The results showed that profits decreased during the pandemic with the average profit earned before the pandemic was Rp 134.137 and the average profit during the pandemic was Rp 35.896.